ANALISA PERCEIVED EASE OF USE DAN PERCEIVED USEFULNESS TERHADAP BEHAVIOR INTENTION PADA APLIKASI DIGITAL PAYMENT OVO - Amadea Rambu Pambudi (Jurnal Strategi Pemasaran, 2019)
The more rapid development of technology, can change the way and behavior of consumers in making purchase transactions. Almost all aspects of life have been digitalized. For example, such as e-commerce, online transportation, and payment systems through digital payment applications. This payment system aims to reduce the use of conventional money to non-cash or cashless. One of the example that is currently actively doing promotions is OVO. OVO is a smart application that provides online payment and transaction services (OVO Cash). This study aims to analyze how the relationship and influence between perceived ease of use and perceived usefulness to the behavior intention on OVO digital payment applications. This research was carried out by distributing 100 questionnaires to 100 OVO user respondents in the Surabaya area. This study uses quantitative analysis techniques and uses multiple linear regression methods. The final results obtained in this study indicate that the variables perceived ease of use have a positive significant effect on the behavior intention. In addition, the perceived usefulness variable also has a significant positive effect on the behavior intention. From the beta coefficient value obtained in the table of multiple regression results, it is found that the variables perceived ease of use have a more dominant influence on the intention behavior than perceived usefulness.